Relationship between objective and subjective markers of muscle recovery in professional handball players - Henze, A.-S.; Matits, L.; Huth, J.; Mauch, F. (International Journal of Sports Physiology and Performance, 2024)
Purpose: To evaluate the relationship between items of the Short Recovery and Stress Scale (SRSS) related to physical stress and recovery and the biomarker creatine kinase (CK) in professional handball.